2018
DOI: 10.1038/s41598-018-20989-8
|View full text |Cite
|
Sign up to set email alerts
|

The anti-mycobacterial activity of the cytochrome bcc inhibitor Q203 can be enhanced by small-molecule inhibition of cytochrome bd

Abstract: Mycobacterial energy metabolism currently attracts strong attention as new target space for development of anti-tuberculosis drugs. The imidazopyridine Q203 targets the cytochrome bcc complex of the respiratory chain, a key component in energy metabolism. Q203 blocks growth of Mycobacterium tuberculosis at nanomolar concentrations, however, it fails to actually kill the bacteria, which may limit the clinical applicability of this candidate drug. In this report we show that inhibition of cytochrome bd, a parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 48 publications
(49 reference statements)
4
67
1
Order By: Relevance
“…To test this hypothesis, the cytochrome bd inhibitor aurachin D was used (Fig. 7A) (47,48). We noted that this inhibitor was not bactericidal to M. bovis BCG (data not shown), as reported for M. tuberculosis (47).…”
Section: Resultsmentioning
confidence: 81%
“…To test this hypothesis, the cytochrome bd inhibitor aurachin D was used (Fig. 7A) (47,48). We noted that this inhibitor was not bactericidal to M. bovis BCG (data not shown), as reported for M. tuberculosis (47).…”
Section: Resultsmentioning
confidence: 81%
“…5C), thus suggesting that Q203 would also have a similar binding mechanism and a similar effect on the activity of M. smegmatis CIII. Indeed, recent studies of the antimycobacterial activity of Q203 on M. tuberculosis and M. smegmatis demonstrated that Q203 targets the bcc complex in both with similar affinity (42). We investigated the in vitro inhibition of M. smegmatis SC III-IV by Q203 by means of the menadiol/oxygen oxidoreductase activity assay and compared the effect with a hybrid supercomplex of M. tuberculosis bcc-CIII and M. smegmatis aa 3 -CIV.…”
Section: Quinone and Quinone Binding Pocketsmentioning
confidence: 99%
“…Recent literature has shown that other QcrB inhibitors (namely, Q203 and TB47) have better efficacy within the acute model of TB infection and when used in combination with first line drugs such as rifampicin and pyrazinamide [30]. Due to the respiratory flexibility of Mtb there have been many reports that the efficacy of QcrB inhibitors might be greatly enhanced by tandem inhibition of the cytochrome bd oxidase based upon in vitro data [21,22,[43][44][45]. However, this dual inhibition concept was strengthened by the impressive in vivo efficacy observed when QcrB inhibitors were evaluated against Mycobacterium ulcerans, a disease-causing strain which lacking cyt-bd oxidase [46][47][48].…”
Section: Resultsmentioning
confidence: 99%